A comprehensive phytochemical, ethnomedicinal, pharmacological ecology and conservation status of Picrorhiza kurroa Royle ex Benth.: An endangered Himalayan medicinal plant. (October 2021) - Bhardwaj, Anikesh; Sharma, Ajay; Cooper, Raymond; Bhardwaj, Garima; Gaba, Jyoti; Mutreja, Vishal; Chauhan, Arjun
Graphical abstract: Highlights: P. kurroa is a perennial herb found in the Himalayas at an altitude of 3500-4800 m. P. kurroa is the most employed Himalayan medicinal plant as traditional medicine. Around 65 bioactive compounds have been isolated from different parts of this plant. P. kurroa is well-known for its use in various immune related disorders. Traditionally, it is used for the cure of asthma, chronic diarrhea and typhoid fever. P. kurroa also known to show wide range of pharmacological activities. Abstract: Secondary metabolites obtained from natural sources have played an important role in health care in modern as well as ancient times. Around 60% of recently approved drugs are prepared using various natural sources. For example, the various traditional medicinal systems like Ayurveda, Yunani and Traditional Chinese Medicines etc., make use of various plant species and their extracts for treatment of numerous human disorders. Picrorhiza kurroa Royle ex Benth. is one of the most employed plant species in traditional medicinal practices of the Himalayan region, specifically, for treatment of various immune related disorders. Furthermore, P. kurroa is widely known for its diverse pharmacological properties: anticancer, hepatoprotective, immunomodulatory, antimicrobial, antioxidant, antiallergic, anti-asthmatic etc. Further, iridoids, terpenoids, flavonoids, phenolic acids, steroids and their glycosides are the key classes of secondary metabolites reported in P. kurroa . However, recent overexploitation of this plant, owing to its wide range of therapeutic potential places it among the list of the endangered medicinal herbs of the Himalayas. Consequently, this review presents up to date data on conservation, agro-techniques, biotechnology, sustainable harvesting, traditional uses, phytochemistry and pharmacological potential of P. kurroa, an important medicinal herb of the western Himalayas.